A Review on the Cytotoxic and Antimicrobial Properties of Xanthones from Cratoxylum cochinchinense: Bioactivities of Cratoxylum cochinchinense - Su Ying Lee; Monjia B C Mojulat; Grace Jebarani Cristhappa Thangaperagasam; Noumie Surugau; Sheri Ann Tan Shu Wei; Oliver D John (Journal of Tropical Life Science, 2023)
Cratoxylum cochinchinense is a perennial plant found in Southeast Asia, having diverse terminologies in various Southeast Asian countries. It has been traditionally used as medicine, tea and food spice. Phytochemical analysis reveals a rich array of bioactive compounds in different parts of the plant such as xanthones, caged xanthones, flavonoids, tocotrienols, triterpenoids, benzophenones and anthraquinones, which obviously possess beneficial biological properties. Among these, xanthones are the most abundant secondary metabolites in C. cochinchinense. This review presents the cytotoxic properties of xanthones present in C. cochinchinense as well as their antimalarial and antibacterial properties, further supporting the medicinal use of this plant.